The Effect of Financial Literacy, Financial Technology, and Digital Marketing Effect on Business Suistainibility in MSMEs in Magelang City - Niagasi, Ariq Fikria; Kurnia, Marlina; Safitri, Wahyu (Innovation, Technology, and Entrepreneurship Journal, 2025)
This article examines "sustainability business in MSME actors in Magelang City. The number of MSMEs in Magelang City in 2023 is 2,126, in addition to 7,805 MSME business actors registered on the Magelang City Government website. This makes the number of MSME actors quite large, making Magelang City superior in prospering their economy. Financial Literacy, Financial Technology, and Effect Digital Marking are indicators used to measure the impact of sustainability business. The research method used is a quantitative approach using the purposive sampling method to 100 respondents. The findings of this study are that financial literacy (tcount 15,945), fintech (tcount 4,970) and effect digital marketing (t count 2,933) either partially or simultaneously affect business susceptibility, all three have a positive influence with a significance number (0.000). It can be concluded that to support the achievement of sustainable business, it is necessary to pay attention to increasing financial literacy, increasing the use of financial technology and developing digital marketing skills